The Impact of Services Quality, Word of Mouths, Facility, Price Towards Customers Satisfaction for Hotel JW Marriott Medan - Thomas (MultiTech Publisher, 2019)
This study investigates the correlation between service quality, word of mouth referrals, facility attributes, pricing, and their collective influence on customer satisfaction at JW Marriott Medan hotel. Through a comprehensive analysis of these factors, the research aims to unveil their relative contributions to overall customer contentment. By discerning the key drivers of satisfaction, this study offers valuable insights to JW Marriott Medan's management for refining their strategies, potentially fostering elevated customer satisfaction, positive reviews, and a competitive edge in the hotel industry